PATHOPHYSIOLOGIC MECHANISMS OF THE INFLUENCE OF TISSUE RESPIRATION ENZYMES ON THE MITOCHONDRIAL FUNCTION IN PATIENTS WITH CHRONIC HEPATITIS C - I.Y. Bagmut; S.M. Gramatiuk (Проблеми екології та медицини, 2018)
Studies conducted over several decades in the field of pathophysiological mechanisms of hepatocyte mitochondria have usually been directed to functional studies of isolated mitochondria in the absence of ADP. In many cases, researchers used data to calculate parameters, including the respiratory rate or the amount of ADP consumed for each amount of oxygen used. However, so far, little is known about how the virus can survive in a highly oxidizing environment, given that oxidative stress is such an outstanding clinical feature that is associated with infection with the hepatitis C virus. In our opinion, adaptation to oxidative stress is a pathophysiological mechanism for the survival of the virus. The objective is to research mechanisms of energy supply disturbance as a mechanism of damage to cells in patients with chronic viral hepatitis C. The 62 HCV+ patients and 24 healthy controls were enrolled in the present cross-sectional study.  The patients were selected on the basis of their stable clinical condition over the past 3 months. The HCV infection was diagnosed by the positivity of anti-HCV and HCV-RNA for at least 6 months of period. Mitochondrial integrity was assessed by cytochrome C release using a commercial kit (Cytochrome C Oxidase Assay Kit, Sigma-Aldrich, St. Louis) indicating a mean of 96% intact mitochondria. Intrinsic NADH fluorescence was monitored in isolated mitochondria as a marker of the mitochondrial NADH redox state. Mitochondrial division is a key determinant of mitochondrial quality control, and HCV modulates these key processes in the adaptation to cellular physiological perturbations associated with infection to promote viral persistence. Mitochondrial division is not invariably associated with cell death but can also protect cells from death induced by oxidative stress and Ca2+-dependent apoptotic stimuli. The mechanism by which enzymes for energy metabolism suppress the replication of the hepatitis C virus is not yet clear, but it probably includes calcium and dissociation of the mammalian replication complex. A detailed understanding of the mechanism by which energy enzymes suppress the replication of HCV infection require additional research.